Pengaruh Affiliate Marketing, Kualitas Produk, dan Promosi Terhadap Minat Beli Konsumen Pada Marketplace Shopee (Studi Pada Mahasiswa Universitas Dian Nuswantoro Semarang) - Ningrum, Lintang Setya; Aryanto, Vincent Didiek Wiet (Peneliti.net, 2024)
This research aims to analyze the influence of Affiliate Marketing, Product Quality and Promotion on Purchase Interest in the Shopee Marketplace positively and significantly. This research is quantitative in nature and involves the student population of Dian Nuswantoro University Semarang, who have made purchases on the Shopee Marketplace. The sampling method used purposive sampling technique, with a total of 107 respondents. The data collection technique uses primary data in the form of a questionnaire whose validity and reliability have been tested. For data analysis techniques, use Smart PLS3 software. This research obtained results that Affiliate Marketing, Product Quality and Promotion had a significant positive influence on consumer buying interest in the Shopee Marketplace by 50.8% and 49.1% was influenced by traffic factors.